STITCHING COSTS TOGETHER: THE LOGISTICS BEHIND TEXTILE PRICING - P, Deepana; Vani, U (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Logistics’ capacity to efficiently handle the flow of resources, information, and items from point of origin to point of consumption makes it an indispensable tool in many facets of business and daily life. This article explores the significant impact of logistics costs on textile pricing, considering factors like transportation, warehousing, customs, handling, supply chain efficiency, technological integration, environmental regulations, economic and political influences. Efficient supply chain management is vital, as it covers stages from raw material procurement to product distribution. This articles also highlights the importance of managing modes of transportation, warehousing, customs compliance and packaging. The role of technology and sustainability in reducing costs is emphasized, along with the impact of economic and political factors. The study underscores the necessity of optimizing logistics to maintain competitive pricing and enhance market for the textile products.